Caracterização e divergência genética de acessos de Physalis spp. a partir de caracteres físico-químicos dos frutos - CUNHA, Carina Raissa Rocha Oliveira da (2023)
The genus Physalis, belonging to the Solanaceae family, stands out for the exotic flavor of its fruits and the presence of bioactive substances. However, as a genetic resource it is still little explored and work involving the genetic improvement of the genus is scarce. Therefore, the objectives of the present work were to characterize and evaluate accessions from the Active Physalis Germplasm Bank at UFRPE, as well as to analyze the genetic divergence between accessions originating from different locations in Brazil, based on physical-chemical characters of its fruits. The experimental design used was completely randomized with five accessions, four replications, three plants per replication, totaling 12 plants per accession, with ten fruits per plant being manually harvested. Physical characteristics (total and fruit fresh mass, width of the calyx and fruit, length of the calyx and fruit, resistance of the fruit skin and pulp, number of seeds per fruit) and chemical characteristics (pH, soluble solids, titratable acidity and ratio). The data were subjected to analysis of variance and the means were compared using the Tukey test. Two grouping methods were used to estimate dissimilarity, in addition to Singh's method to identify the relative contribution of characters and Pearson's correlation. The results showed genetic variability between the accessions, forming two distinct groups in the clusters, with the ascending hierarchical classification algorithm being more discriminatory. The dissimilarity coefficients indicate that the most divergent accessions in the population were BAG_P20 and BAG_P33, which can be used in crosses.